Dahlmanac 2: fun facts and jokes with roald dahl - Blake, Quentin; Woodward, Kay (Puffin London, 2007)
Interesting diseases, the most heroic animals, beards, disguises, quizzes and pirates appear in the second fun-filled collection of facts, activities and jokes to celebrate Roald Dahl Day. 'Dahlmanac 2' is jam-packed with treats - some disgusting, some delicious - stuff that every Roald Dahl fan should know